Direct and indirect impacts of crop–livestock organization on mixed crop–livestock systems sustainability: a model-based study. (11th May 2016) - Sneessens, I.; Veysset, P.; Benoit, M.; Lamadon, A.; Brunschwig, G.
Abstract : Crop–livestock production is claimed more sustainable than specialized production systems. However, the presence of controversial studies suggests that there must be conditions of mixing crop and livestock productions to allow for higher sustainable performances. Whereas previous studies focused on the impact of crop–livestock interactions on performances, we posit here that crop–livestock organization is a key determinant of farming system sustainability. Crop–livestock organization refers to the percentage of the agricultural area that is dedicated to each production. Our objective is to investigate if crop–livestock organization has both a direct and an indirect impact on mixed crop–livestock (MC–L) sustainability. In that objective, we build a whole-farm model parametrized on representative French sheep and crop farming systems in plain areas (Vienne, France). This model permits simulating contrasted MC–L systems and their subsequent sustainability through the following indicators of performance: farm income, production, N balance, greenhouse gas (GHG) emissions (/kg product) and MJ consumption (/kg product). Two MC–L systems were simulated with contrasted crop–livestock organizations (MC20 –L80 : 20% of crops; MC80 –L20 : 80% of crops). A first scenario – constraining no crop–livestock interactions in both MC–L systems – permits highlighting that crop–livestock organization has a significant direct impact on performances that implies trade-offs between objectives of sustainability. Indeed, the MC80 –L20 system is showing higher performances for farm income (+44%), livestock production (+18%) and crop GHG emissions (−14%) whereas the MC20 –L80 system has a better N balance (−53%) and a lower livestock MJ consumption (−9%). A second scenario – allowing for crop–livestock interactions in both MC20 –L80 and MC80 –L20 systems – stated that crop–livestock organization has a significant indirect impact on performances. Indeed, even if crop–livestock interactions permit improving performances, crop–livestock organization influences the capacity of MC–L systems to benefit from crop–livestock interactions. As a consequence, we observed a decreasing performance trade-off between MC–L systems for farm income (−4%) and crop GHG emissions (−10%) whereas the gap increases for nitrogen balance (+23%), livestock production (+6%) – MJ consumption (+16%) – GHG emissions (+5%) and crop MJ consumption (+5%). However, the indirect impact of crop–livestock organization doesn't reverse the trend of trade-offs between objectives of sustainability determined by the direct impact of crop–livestock organization. As a conclusion, crop–livestock organization is a key factor that has to be taken into account when studying the sustainability of mixed crop–livestock systems.